Nosocomial infection in the Intensive Care Unit - Sh Ghiasvandian (Tehran University of Medical Sciences, 2002)
Nosocomial infection is occured subsequent to admitting patients to the hospital. This infection is usually accompanied by a significant mortality and morbidity and it causes therapeutic costs to be increased.The factors interfering nosocomial infection are some organisms that are either resistant to antibiotics or they will become resistant to them.Nearly 5-10% of the patients admitted to the hospitals are infected with a sort of infection.The infection in patients hospitalized in the intensive care unit (ICU) is in close relationship with the appearance of clinical side effects and results in economical and human damages. It is reported that 25% of the entire nosocomial infection in ICU is transferred through blood and respiration.Since 1% of the nosocomial infection is preventable and nurses are fully aware of its controlling methods, however, there are incoordination in performing those methods and insufficient control of the infection. Therefore, the prevention strategies and nosocomial infection control are important cases to be considered in order to achieve more effective therapeutic results concerning the patients who suffer from nosocomial infection.